Effect Of Using Chicory Waste Silage (Brassica Pikenensia L.) in Rations on The Performance and Efficiency Of Grower Pig Rations - Baaf, Nofiyanti; Suryani, Ni Nengah; Yunus, Marthen (Journal of Tropical Animal Science and Technology, 2025)
The purpose of this study was to evaluate the effect of using chicory (Brassica pekinensia L.) waste silage in rations on the performance and efficiency of grower pig rations. Twelve landrance breed pigs aged 3-4 months with an initial body weight of 28-52 kg, average 36 kg (KV = 17.72%), were used in this study. Experiment method a Randomized Block Design (RBD) consisting of 4 treatments and 3 replications this study used. The treatments were R0: 100% Basal Rations (BR); R1: 90% BR+10% Chicory Waste Silage (CWS); R2: 85%RB+ 15% CWS; R3: 80% RB+20% CWS. The variables studied were ration consumption, body weight gain, ration conversion and ration efficiency. The results of the analysis of variance showed that the treatment had no significant effect (P>0.05) on the performance and efficiency of the pig rations in the study. It was concluded that the use of chicory waste silage 10%, 15% and 20% in the ration had the same effect on ration consumption, body weight gain, ration conversion and ration efficiency. Chicory waste silage can replace up to 20% of basal feed.